PERAN AKUNTABILITAS DAN PENGETAHUAN TERHADAP KUALITAS HASIL AUDIT DENGAN MODERASI SIKAP MENTAL AUDITOR - Raden Susana Suspayati; Syahril Djaddang; Darmansyah Darmansyah (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2018)
In order to guarantee quality audit results, each auditor explains the Auditing Standards. This study aims to determine the effect of accountability and knowledge on the quality of audit results with auditor's mental attitude as moderation. In this research survey method was used. The variables studied were independent variables including accountability, knowledge, and dependent variable was the quality of audit results, with the auditor's mental attitude as moderation variable. The samples were 80 auditors from KAP Kanaka Puradiredja, Suhartono, KAP Albert Silalahi Rekan, and KAP S. Mannan, Ardiansyah Rekan. The data was collected by questionnaire to measure perception of the auditor related to the variables tested. The technique of processing and data analysis was using Warp PLS 6.0 with Equation Model of Goodness of Fit Model. The results of this research: (1) there was no influence on accountability variable to audit result quality, and there was no accounting moderator to audit result quality. (2) There was a positive significant influence on the knowledge variable on the quality of the audit result (3). There was a significant positive effect on the auditor's mental attitude variable on the quality of audit results.